Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

Commoning care: Feminist degrowth visions for a socio-ecological transformation - Dengler, Corinna; Lang, Miriam (Feminist Economics, 2022)
This paper addresses the question of how to organize care in degrowth societies that call for social and ecological sustainability, as well as gender and environmental justice, without prioritizing one over the other. By building on degrowth scholarship, feminist economics, the commons, and decolonial feminisms, we rebut the strategy of shifting yet more unpaid care work to the monetized economy, thereby reinforcing the separation structure in economics. A feminist degrowth imaginary implies destabilizing prevalent dichotomies and overcoming the (inherent hierarchization in the) boundary between the monetized economy and the invisibilized economy of socio-ecological provisioning. The paper proposes an incremental, emancipatory decommodification and a commonization of care in a sphere beyond the public/private divide, namely the sphere of communitarian and transformative caring commons, as they persist at the margins of capitalism and are (re-)created by social movements around the world.HIGHLIGHTS Degrowth aims at creating human flourishing within planetary boundaries.As feminist degrowth scholarship, this study discusses degrowth visions for care work.It problematizes the shifting of yet more unpaid care work to the monetized economy.Instead, it proposes collective (re)organization in the sphere of the commons.Caring commons are no automatism for a gender-just redistribution of care work.
Keywords: approches et analyses; care; discipline; décroissance; environnement; féminisme décolonial; projet charge mentale; sciences de la gestion; thématiques; travail; travail du care; économie

A gender-responsive employment recovery: Building back fairer - EMPLAB (International Labour Organization, 2020)
La crise du COVID-19 est différente des crises économiques précédentes dans sa profondeur et son ampleur, car des vies sont perdues, l'emploi et les moyens de subsistance sont menacés et les économies se contractent considérablement. Comme pour les crises précédentes, cependant, ses conséquences ne sont pas subies de la même manière. Comme aucune autre auparavant, cette crise a mis à nu les inégalités entre les sexes enracinées qui, aggravées par d'autres inégalités, affligent les marchés du travail. La crise du COVID-19 a un impact différent sur les femmes et les hommes, selon le secteur dans lequel ils travaillent, la fragilité de leur situation d'emploi, leur accès au travail et à la protection sociale, et leurs responsabilités familiales. Cette note montre que cette fois-ci, les emplois des femmes sont relativement plus à risque que ceux des hommes, et dans un contexte qui se détériore rapidement, les femmes les perdent plus rapidement que les hommes. Même si elles sont moins graves, les crises précédentes offrent quelques leçons de prudence pour la crise actuelle. Ils illustrent que lorsque les emplois sont rares, les femmes sont privées d'opportunités économiques et de sécurité par rapport aux hommes. Ces crises impliquent généralement l'érosion des protections du travail et la détérioration durable des conditions de travail. Et que les femmes ne sont pas seulement touchées par la perte d'emplois, mais aussi par les réductions de dépenses qui contractent la fourniture de services publics, en particulier les services de soins. Dans ce contexte, les politiques de l'emploi, y compris les politiques macroéconomiques, sectorielles et du marché du travail, doivent placer l'égalité des sexes au cœur des efforts d'urgence et de relèvement afin d'éviter des dommages à long terme aux perspectives d'emploi des femmes et de reconstruire mieux et plus juste. Cette note indique quatre priorités politiques pour une reprise sensible au genre : empêcher les femmes de perdre leur emploi ; éviter un assainissement budgétaire prématuré ; investir dans les soins; et se concentrer sur des politiques de l'emploi sensibles au genre.
Keywords: OFDIG; approches et analyses; care; covid-19; discipline; inégalités; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; travail; économie; égalité femme*-homme

Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (University of Minnesota Press, 2009)
"A nuanced critique of how the World Bank encourages gender norms through its policies, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations.By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world's largest and most influential development institution. Looking concurrently at economic and gender policy, Bedford connects reform of markets to reform of masculinities, loan agreements for export promotion to pamphlets for indigenous adolescents advising daily genital bathing, and attempts to strengthen institutions after the Washington Consensus to efforts to promote loving couplehood in response to economic crisis. In doing so, she reveals the shifting relationships between development and sexuality and the ways in which gender policy impacts debates about the future of neoliberalism.Providing a multilayered account of how gender-aware policies are conceived and implemented by the World Bank, Developing Partnerships demonstrates as well how institutional practices shape development."– Site de l'éditeur.
Keywords: LGBTQIA2+; approches et analyses; care; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

Measuring care: Gender, empowerment, and the care economy - Folbre, Nancy (Journal of Human Development, 2006)
How should “care” be defined and measured in ways that enhance our understanding of the impact of economic development on women? This paper addresses this question, suggesting several possible approaches to the development of indices that would measure gender differences in responsibility for the financial and temporal care of dependents.
Keywords: care; discipline; macroéconomie; projet charge mentale; périodes; sciences de la gestion; soins aux personnes dépendantes; thématiques; travail; travail invisible; économie

Des questions sur la culture organisationnelle des organismes communautaires - Guberman, Nancy; Fournier, Danielle; Belleau, Josée; Beeman, Jennifer; Gervais, Lise (Nouvelles pratiques sociales, 1994)
Cet article décrit la problématique et les cinq dimensions d'analyse d'une recherche portant sur les cultures organisationnelles propres aux organismes communautaires au Québec. Dans un premier temps, nous examinons en quoi la notion de culture organisationnelle peut être une piste utile dans l'identification de la « différence » des organismes communautaires. Ensuite, nous cernons, à partir d'une recension des écrits, ces différences par rapport aux organismes du réseau et soulignons les éléments organisationnels spécifiques aux groupes de femmes. Enfin, nous présentons le contenu de nos cinq dimensions d'analyse. Il s'agit des modes de gestion, du rapport aux membres, du rapport au travail salarié, du rapport à la vie privée et du rapport à l'Etat. Il est primordial de mieux cerner la spécificité des pratiques et les éléments de la culture organisationnelle des groupes communautaires pour mettre en valeur leur apport au renouvellement des pratiques sociales.
Keywords: amérique du nord; amériques; canada; care; discipline; groupes de femmes; intervention sociale; organisation et ressources humaines; organisme communautaire; québec; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; travail du care